PERSEPSI PELANGGAN TERHADAP LISTRIK PINTAR - ., Johannes; ., Novitasari; Amalia, Winda Lara (Jurnal Dinamika Manajemen, 2014)
Smart electrecity or prepaid electricity is introduced by PLN as program that has many goals namely; for customer need fulfilment, citizen, and PLN. On the customer level, goal establishment determinants are complex, one of them is customer perceptions on smart electrical fitting performance. This research is aimed at revealing concumer perception on some atributes they are: performance, feature, reliability, conformance, durability, service ability, and perceived quality. Research method use survey that used descriptive and qualitative approach. Research result shows that atributes generally has high score, and highest one is servicisability (4.16). Hence, smart electricity attibutes is perceived good by customers. Future related research on smart electricity is how is the household involevement and communication model that build by PLN to increase the customers. Key Words: Prepaid, KwH, Selfcustom and Region